Sistem Pendidikan Islam Dan Perannya dalam Arena Global Perspektif Filsafat, Teori Dan Kurikulum - Nanang Abdillah (FATAWA: Jurnal Pendidikan Agama Islam, 2020)
Where should the future direction of Islamic education be taken? A classic question that often arises but is also challenging for the academic community to always provide answers. I don't know who is wrong, until now, the general public still has a less favorable perception of Islamic education. In fact, there are still many choices of parents to enter their children into Islamic education as the second choice after the first choice to general education institutions. There is a problem for the academic community of Islamic education to continue their identity so that it is more accessible to the wider community. Because of that, Islamic education must always provide resources to its education so that it is relevant to the development of its community. So that the direction of Islamic education in the future does not just follow the current changes that have occurred, Islamic education needs to rethink its philosophy, theory, and educational curriculum. Thus Islamic education will not lose its identity, but what happens is that Islamic education will not play an active role in the current global social flow